Nova Aetas: astronomy research and visitors centre - Raffner, Philippe Angelo (My University, 2012)
Astronomy in South Africa remains one of the most uncelebrated of the natural sciences, this despite the country’s almost 200 year history of involvement in its international development and proud contemporary standing in its practice. This is largely because South Africa has only greatly dispersed and inadequate avenues through which the public can broaden its knowledge of astronomy and its many related disciplines. The Nova Aetas Astronomy research and visitor’s centre aims to rectify this situation through the creation of a new place for Astronomy in South Africa, one which will create both a new formal hub for the science as a profession and also stand as a new facilitator of public astronomical education. Through doing this, the centre will allow for a public emersion and experience in and of all avenues of Astronomical practices in South Africa. The centre will do this though its use of functional program, the appropriate choice of site and several unique and relevant architectural styles and devices. The intention of the project raises several important discussions surrounding these afore mentioned criteria. Firstly one must consider the choice of site and determine a project placement which is relevant to the practice of astronomy, both in a contemporary and historic sense, within the broader context of South Africa. After a series of investigations the site of the Old Royal Observatory in Observatory, Cape Town, was chosen as the location of the project. This was due to its strong historic ties to the birth of South African Astronomy, its modern day connection to the South African Astronomical Observatory for which it currently serves as headquarters, its strong degree of public regard and ease of public accessibility, Using both the public and private functional models of the present day observatory as precedent, an appropriate series of new functional programs can be developed to ensure the correct facilitation of the project’s key intentions of public integration and emersion. Finally one must decide upon what aesthetic devices and architectural languages should be used in the generation of the centre’s design. This was done through an in-depth analysis of the relationship between astronomy and architecture throughout the ages- isolating key lessons learned during each epoch of realisation. Contained in this document are written accounts of these various explorations (Chapters 1-5), supported by relevant imagery and graphic explorations and a detailed explanation of how each of these explorations were interpreted into the final design of the Nova Aetas Centre and finally an in depth explanation and analysis of the proposed Nova Aetas design